Resistance to leptin-replacement therapy in Berardinelli–Seip congenital lipodystrophy: an immunological origin - Beltrand, Jacques; Lahlou, Najiba; Le Charpentier, Tifenn; Sebag, Guy; Leka, Sofia; Polak, Michel; Tubiana-Rufi, Nadia; Lacombe, Didier; de Kerdanet, Marc; Huet, Frederic; Robert, Jean-Jacques; Chevenne, Didier; et al. (European journal of endocrinology, 2010)
ContextRecently, in a 4-month proof-of-concept trial, beneficial metabolic effects were reported in non-diabetic children with Berardinelli–Seip congenital lipodystrophy (BSCL); this information prompted us to hypothesize that long-term leptin-replacement therapy might improve or reverse the early complications of the disease in these patients.Patients and methodsA 28-month trial was implemented in eight patients. Efficacy assessment was based on a decrease in serum triglyceride concentrations, and/or a decrease in liver volume and/or an increase in insulin sensitivity of at least 30% respectively. The response was defined as follows: total (3/3 positive criteria), partial (1 or 2/3), or negative (0/3). Anti-leptin antibodies were measured with a radiobinding assay, and a neutralizing effect was assessed in primary cultures of embryonic neurons incubated with an apoptotic agent (N-methyl-d-aspartate) and the patient serum, with or without leptin.ResultsA negative or partial response to treatment was observed in five of eight patients even when leptin dosages were increased. A displaceable leptin binding was detectable in all patients after 2 months of treatment. At 28 months, binding was higher in the patients with a negative response than in the total responders, and it paralleled both the increase in leptin dosage and serum leptin concentrations. Co-incubation of embryonic neurons with serum from two patients with a negative response inhibited the neuroprotective effect of leptin.ConclusionUnder leptin therapy, patients with BSCL may develop a resistance to leptin, which could be partly of immunological origin, blunting the previously reported beneficial effects.